PROBABILISTIC CHARACTERISTICS OF THE SECTIONS OF THE ROLLING STOCK CUTS ON THE ARROWS - Bobrovskiy, V. I.; Kudriashchov, O. V.; Chibisov, Yu. V. (Science and Transport Progress, 2007)
The method of calculation of probabilities of discontiguous cuts’ divisions on the switch points is developed. The researches as for connection these probabilities with the parameters of the trains are executed. The researches also tackle the problem of the connection between the above mentioned probabilities and the construction of the hump neck.